Exercise-induced bronchial asthma: issues of prevention and requirements of WADA - Gunina Larisa (National University of Physical Education and Sport of Ukraine, 2016)
The paper shows that exercise-induced bronchial asthma, even when induced directly by professional activity of an athlete, has in its basis the violation of the morphological, immunological and biochemical mechanisms, as well as has clear diagnostic criteria. The modern pedagogical, organizational and pharmacological methodologies are highlighted for prevention of bronchospasm, which determines the severity of athlete's condition and makes impossible further physical activity. The potential for the use of various drugs was analyzed in view of the fact that many of them are today included in the World Anti-Doping Agency list of prohibited substances .